PENGARUH KUALITAS, PERSEPSI NILAI, CITRA, DAN KEPUASAN TERHADAP LOYALITAS ATAU KEINGINAN BERPINDAH PENUMPANG BUS TRANSJOGJA - Petra Surya Mega Wijaya; Jonathan Herdioko (Fakultas Bisnis UKDW, 2010)
This research is not only focused on satisfaction, but also thevariables that form satisfaction, which are core quality, relationalquality, image, and perceived value. The modeling on this research is objected on the TransJogja transportation mode. The problem formulation on the research here are core quality, service quality, image, and perceived value which relates with satisfaction, and how satisfaction relates to loyalty and switching intention. There were 200 TransJogja passengers randomly chosen in this research and the data processing uses SEM (Structural Equation Model). The results show that only core quality and relational quality are significant to satisfaction, while image and perceived value does not relate to satisfaction. Satisfaction does not also relate to loyalty and switching intention.Keywords: core quality, relational quality, image, perceived value, satisfaction, loyalty, switching intention, TransJogja, SEM